Risk factors in adolescents as predictors of arterial hypertension in adults: Protocol for a systematic review. - Márcia Gisele Santos da Costa; J Jaime Caro; Katia Vergetti Bloch (PLoS ONE)
This is a protocol of a review paper, and there is no abstract. This review is part of a doctoral project that aims to develop a discrete event simulation model to predict how many adolescents may become hypertensive in adulthood. We will use data from the Brazilian study of cardiovascular risks in adolescents, called ERICA (Portuguese acronym). This study may help promote adherence to disease prevention protocols.